Mechanism on reduction swelling of pellets prepared from Bayan Obo iron ore concentrate. (26th November 2021) - Fan, Yingjie; Zhang, Yunhao; Li, Zhichao; Chai, Yifan; Wang, Yici; Luo, Guoping; An, Shengli
ABSTRACT: The composition of Bayan Obo iron ore concentrate is complex. If a large proportion is used to prepare pellets, abnormal swelling will occur during blast furnace smelting. This paper studies the swelling behavior of pellets prepared from Bayan Obo iron ore concentrate in stages during the reduction process; XRD and SEM-EDS analysis and calculates the crystal parameters of the reduction products in each stage. The results show that the total RSI of pellets prepared from Bayan Obo iron ore concentrate is as high as 35%, and the third stage of reduction has the maximum swelling rate, which is 24%. The mechanisms of the three stages reduction swelling of pellets are the crystal transformation, the effect of slag phase and the growth of iron whiskers. The results can enrich the reduction swelling theory of pellets prepared from complex intergrowth minerals.